Advances in Knowledge Management:Celebrating Twenty Years of Research and Practice - Bolisani, Ettore (Springer, 2015)
This book celebrates the past, present and future of knowledge management. It brings a timely review of two decades of the accumulated history of knowledge management. By tracking its origin and conceptual development, this review contributes to the improved understanding of the field and helps to assess the unresolved questions and open issues.